1995
DOI: 10.1007/bf01857867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of binge eating on the prediction of weight loss in obese women

Abstract: Factors that may be associated with successful weight loss in the obese are of clinical and theoretical significance. Although perceived behavioral control (PBC) had been shown to predict weight loss in a nonclinical population, it had not been used to predict weight loss in the obese. We studied obese women enrolled in a 15-week structured weight loss program and hypothesized that PBC would predict weight loss for low binge eaters better than for high binge eaters. Results indicated that the ability of PBC to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Because parents control the outdoor activities of their children to a large extent (Ryan & Stiller, 1991), it is obvious that significant others play an important role in maintaining an observed change. Given the important role of 'significant others' and the social influences in the formation of adolescents' intention and behaviour (Aj-Zen, 1988;Smith, Sondhaus, & Porzelius, 1995;Hausenblas, et al, 1997;Smith & Biddle, 1999;Hagger, et al, 2002)) later interventions should incorporate education of members of the social environment on the behaviour at hand, i.e., provide information to parents about the benefits of exercise and the negative outcomes of unhealthy lifestyles. Theodorakis (1994) defined role identity as the integration of a repeated behaviour into the self.…”
Section: Discussionmentioning
confidence: 99%
“…Because parents control the outdoor activities of their children to a large extent (Ryan & Stiller, 1991), it is obvious that significant others play an important role in maintaining an observed change. Given the important role of 'significant others' and the social influences in the formation of adolescents' intention and behaviour (Aj-Zen, 1988;Smith, Sondhaus, & Porzelius, 1995;Hausenblas, et al, 1997;Smith & Biddle, 1999;Hagger, et al, 2002)) later interventions should incorporate education of members of the social environment on the behaviour at hand, i.e., provide information to parents about the benefits of exercise and the negative outcomes of unhealthy lifestyles. Theodorakis (1994) defined role identity as the integration of a repeated behaviour into the self.…”
Section: Discussionmentioning
confidence: 99%
“…Similar in theory, the TPB suggests that in addition to attitudes and subjective norms, perceived behavioral control also contributes to the prediction of behavioral intentions (Ajzen 1991). The TPB is more predictive of intentions than the theory of reasoned action in cases in which the behavior is not completely under the actor's volitional control (for example, weight loss; Smith et al 1995;smoking;Norman et al 1999). Many behaviors, including the various forms of romantic partner abuse, may not be under complete volitional control (Tolman et al 1996).…”
mentioning
confidence: 92%
“…1,2 One group of behavioural traits that may generate imbalance in the energy regulation by increasing energy intake, and hence possibly relate to obesity and weight gain, are abnormal eating patterns such as restrained eating, binge eating and night eating. [3][4][5][6][7][8][9][10] The night-eating syndrome was described in 1955 as a condition characterised by morning anorexia (minimal or no calorie intake at breakfast), evening hyperphagia (at least 50% of daily calorie intake after the evening meal) and insomnia, and it has later been broadened to include night time awakenings with food intake. [11][12][13][14] Several studies have used this definition and found frequencies of the night-eating syndrome ranging from 8 to 27% among obese patients.…”
Section: Introductionmentioning
confidence: 99%